The chairs of hereditary cancer: understanding time and illness using creative ethnographic drawing - Noronha, Susana de (2019)
Using scientific illustration, this article aims to examine how time is experienced, understood, and managed in hereditary malignancies, analysing the breast cancer story of a Portuguese woman with BRCA1/2 mutations. Blending lived experience, anthropology, and art, this text results from a transdisciplinary qualitative exercise, incorporating embodied knowledge, speech, and creative ethnographic drawing at the core of the research, using them as methodological and heuristic resources. Based on a narrative collected in an informal interview, it suggests the use of visual and creative methodologies aimed at a reinforced understanding of cancer. Combining text and images, we will analyse the multiple meanings of time that permeate this story, searching for the experiences, uses, and meanings of moments of waiting, interruption, slowness, delay, urgency, and acceleration, before, during and after illness and treatment, using and drawing chairs, as concrete objects and metaphors, to give them form. Waiting emerges as the most relevant experience to understand her hereditary cancer story, linking past, present, and future within a form of suffering that minimizes physical pain.